AESTHETICS AND ETHICS OF THE SUSTAINABLE ORGANIZATIONS - Colombo, Gianluca; Gazzola, Patrizia (European Scientific Journal, ESJ, 2014)
The paper aims to analyse the strong links between the company and the local community. We live a very fragile condition at both micro level and at macro level. The most solid organizations (companies, foundations, non profit) feel the uncertainty that oppresses visionary leaps and crushes the passions of employees. At macro level, national governments and supranational organizations don’t show the capacity to react and to project in an adequate way to the complexity of the problems. The two aspects are usually treated individually by separate disciplines. We argue that separating points of view don’t improve the skills of analysis and diagnosis, nor the strategic and political intervention. To understand the union between company and local communities we analyse two Italian companies, known for their responsible actions: Olivetti and Luxottica. The first belongs to our past: 1950s. For Adriano Olivetti, the company is a community of people pursuing a common good through combinations of labour and capital. The ethics of the common good has been directly involved in the economic governance of the company. The second is a current example of innovative governance based on the human aspects of organizational life and on the quality of relationships among people. Luxottica has developed as a subject in itself with humanity, a human community in the full meaning of the term. Both examples show that the stress of the economic performance is combined synergistically with the development of the local community; in this ago-antagonist relationship the aesthetic dimension plays a non-additional role.